Study on Thermal Reflection Characteristics of Composite Inorganic Coatings - Jun Shang; Mingyang Wang; Pei Wang; Guoliang Li; Mengyao Yang; Yang Li (Applied Sciences, 2024)
This study examined the thermal reflective properties of composite inorganic coatings applied to various wall types. It evaluated the influence of these coatings on the thermal insulation and reflectivity of the walls. The findings indicate that coating application markedly enhances a wall’s thermal insulation capabilities and increases its heat flux reflection ratio. These results offer crucial theoretical backing and practical guidance for the future use of coating technologies in construction. By refining the coating formulations and application processes, the thermal insulation properties of walls can be further enhanced, thus making a significant contribution to building energy efficiency and environmental protection. Consequently, this research provides essential references and insights for advancing coating technology in the construction industry.